PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA NYARING SISWA KELAS IV SDN 008 SUNGAI BAKAU - ', Rosidah; Antosa, Zariul; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated because of the low ability to read the fourth grade students of SDN 008 Sungai Bakau, with the average value of only 56.4 sedngkan KKM is 70. This research aims to improve the ability to read aloud the fourth grade students of SDN 008 Sungai Bakau. This research is a classroom action research (PTK), which consists of two cycles, held on genab semester of 2015/2016. Subjects of this study amounted to 20 students. This study aims to improve the ability to read aloud using the approach Contextual Teaching and Learning (CTL). The research instrument consists of learning tools and instrument data collecting observation sheets and assay results of learning. Data analysis technique used is the statistical analysis using the manual method. Data analysis activities of teacher and student activity sheets based on data observed during the implementation of the action. While the analysis of learning outcomes data derived from the results of the final test cycles one and two. Based on data analysis activities of teachers and students saw an increase include: the activities of teachers in the first cycle reached 67.5%, the second cycle to 80% while the student activity reached 62.50% the first cycle, the second cycle reaches 87.50%. Analysis of the data showed an increase in student learning outcomes, namely 68.75 in the first cycle increase in cycle two to be 79.87. This indicates that the application of CTL learning model can improve the ability to read aloud the fourth grade students of SDN 008 Sungai Bakau. Key Words: Model Contextual Teaching and Learning, The ability to read aloud